QTL Mapping for Dough Mixing Characteristics in a Recombinant Inbred Population Derived from a Waxy × Strong Gluten Wheat (Triticum aestivum L.) - Fei-fei ZHENG; Zhi-ying DENG; Cui-lan SHI; Xin-ye ZHANG; Ji-chun TIAN (Journal of Integrative Agriculture, 2013)
Protein and starch are the most important traits in determining processing quality in wheat. In order to understand the genetic basis of the influence of Waxy protein (Wx) and high molecular weight gluten subunit (HMW-GS) on processing quality, 256 recombinant inbred lines (RILs) derived from the cross of waxy wheat Nuomai 1 and Gaocheng 8901 were used as mapping population. DArT (diversity arrays technology), SSR (simple sequence repeat), HMW-GS, and Wx markers were used to construct the molecular genetic linkage map. QTLs for mixing peak time (MPT), mixing peak value (MPV), mixing peak width (MPW), and mixing peak integral (MPI) of Mixograph parameters were evaluated in three different environments. The genetic map comprised 498 markers, including 479 DArT, 14 SSR, 2 HMW-GS, and 3 Wx protein markers, covering 4 229.7 cM with an average distance of 9.77 cM. These markers were identified on 21 chromosomes. Eighteen additive QTLs were detected in three different environments, which were distributed on chromosomes 1A, 1B, 1D, 4A, 6A, and 7D. QMPT-1D.1 and QMPT-1D.2 were close to the Glu-D1 marker accounting for 35.2, 22.22 and 36.57% of the phenotypic variance in three environments, respectively. QMPV-1D and QMPV-4A were detected in all environments, and QMPV-4A was the nearest to Wx-B1. One minor QTL, QMPI-1A, was detected under three environments with the genetic distances of 0.9 cM from the nearest marker Glu-A1, explaining from 5.31 to 6.67% of the phenotypic variance. Three pairs of epistatic QTLs were identified on chromosomes 2D and 4A. Therefore, this genetic map is very important and useful for quality trait related QTL mapping in wheat. In addition, the finding of several major QTLs, based on the genetic analyses, further suggested the importance of Glu-1 loci on dough mixing characteristics.